Synthesis and evaluation of D-cycloserine analogues against mycobacterium tuberculosis - Renga, Shoneeze Simone (Department of Chemistry, 2021)
Tuberculosis (TB) continues to be the leading cause of death from a single infectious agent worldwide. The rapid emergence of multidrug-resistant and extremely drug-resistant underpin the urgent need for novel, safe and efficacious drugs. D-Cycloserine (DCS) is an oral bacteriostatic anti-tubercular drug used for the treatment of drug-resistant TB. Despite attractive properties, DCS displays significant toxicity at effective dosages. However, a synthetic analogue of DCS, terizidone, has shown an improved safety profile. This study focused on the synthesis of two new classes of DCS analogues: isoxazolidin-3-oneimines (ISIs) and 3-isoxazolidin-4-yl amides (ISAs). These analogues were designed to act as potential prodrugs. In an effort to explore structure-activity-relationships, a total of 17 compounds were synthesized, fully characterized, and evaluated in vitro for their antimycobacterial activity against the drug-susceptible Mtb H37Rv strain cultured in 7H9/ADC media. Of these, two compounds displayed noteworthy antimycobacterial activity (MIC99 ≤ 10 μM). In addition to this, all 17 compounds manifested low cytotoxicity (IC50 > 25 μM) when tested in vitro against the chinese hamster ovarian cells and the human hepatocytes cells. Furthermore, a selected potent compound displayed high microsomal metabolic stability in rat, mouse and human liver microsomes. The kinetic solubility of the target compounds was determined using a HPLC-based method. The solubility data obtained was then correlated with melting point, tPSA and cLogP in order to establish structuresolubility relationships across the two compounds series. Solubility was strongly correlated to melting point in the IZAs series (R2 = 0.9318) and moderately correlated to tPSA for IZIs (R2 = 0.164, whereas there was no correlation between solubility and cLogP (lipophilicity) in either class of compounds (R2 = 0.085 for IZIs and R2= 0.0004 for ISA).